Cultura politica di partito e cultura politica nazionale: il caso del Pci nella Prima Repubblica - Millefiorini, Andrea (SocietàMutamentoPolitica, 2016)
In the paper we are explaining those aspects of the Italian Communist Party, that, thanks to the particular organized structure, contributed, in a meaningful way, to outline some characteristic features of the Italian political culture. There are four aspects of them: the first one was represented by a strong level of ideologism that for reaction and contamination passed from its main centre of diffusion (which was just the P.C.I) to the other actors of the Italian party system, whose high level of ideologization produced models of interpretation of problems and of decisions, elaboration and planning, about not so much pragmatic plans; on the contrary, concerning rhetoric or propagandistic approaches.A second, relevant effect to which contributed in this case not only the political communist culture, we are analyzing above all from this point of view: it was constituted by the leadership exerced by the political parties that acquired in the symbolic values of the Italians universe as regards the other components of the Political system; the consequences of this situation we are going to analyze in the paper.A third element was the strong statalism which constituted the political culture of the country at least till the end of seventies.The fourth factor spread by the political communist culture was given by the egualitarianism. It assumed a relevant role at the organizing and structural level concerning the burocratic machinery; the values connected to it not always produced good results in efficiency, in resources optimization and productivity.